PENDUGAAN KEPEKAAN KAYU KARET TERHADAP SERANGAN KUMBANG AMBROSIA - Paimin Sukartana (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
An experiment to assess the susceptibility of rubber wood (Hevea brasiliensis) to ambrosia beetle infestations was conducted in a rural area, near a rubber plantation in Jasinga, Bogor. Fresh cut rubber wood, each of 75 cm in length 1:1 and of about 25 cm in diameter, were prepared for four treating conditions including freshly cut, debarked, and coated with flint kote, and (in a prepared bore hole made on the middle of test logs with 2.5 methanol 96%. The extent of the beetle infestations were then observed and recorded.The test results revealed that the degree of rubber log susceptibility to ambrosia beetle infestations was affected by the treatments. The debarked logs were highly infested by the beetles in less than nine days after the treatment while the un barked ones were still soundly left in the field for more than one month. Significant increase in log susceptibility due to the treatments with ethanol and flint kote was also recorded even though the beetle infestations were not so high then those on the debarked ones.